Propuesta de un plan de comunicación interna para mejorar el clima laboral y sentido de pertenencia en Isatex - Hayek Ponce, Juan Pablo (2014)
This research document has been developed over the relation among the employees of Isatex as how they feel about their working place. Based on Humanistic Theory and three mainstays: internal communication, sense of ownership and working environment. Those mainstays gave us a better understanding of the actual state of Isatex (internally speaking). Theories of different corporate communicators such as: Francisca Morales, Alejandro Formanchuk, Federico Gan, David Caldevilla, among others, were the support of the theoretical frame. An assessment that allowed me to develop the methodology that was applied during the investigation, which lead me into providing an improvement plan over the internal communication and the sense of ownership of the employees towards Isatex. In order to accomplish the best results for the working environment, this work used a multi-modal approach that included: employee survey and research interviews with Ing. Luis Issa Yarad -chief executive- as well as the supervisors. This way I managed to gather information, personal opinions and data; that was really useful to shape the improvement plan, which I already mention, paying special attention on the ownership sense. The results and conclusions on this research paper reflect on the high importance and relevance that the employers shut put on a constant motivation of the management to create ties between other areas. The goal should be to promote proactive employees that care for their working place, to develop a compromise with it. Take care of the inter-relations, work on the internal communication and work towards having a pleasant working environment at Isatex.